The Role of Village Heads in Increasing Participation in Mutual Cooperation Activities in Jia Village, Sape District, Bima Regency - Misrawati Misrawati (FKIP, Universitas Palangka Raya, 2023)
The objectives of this research are, a) The role of the village head in planning community participation in gotong royong activities, b) The role of the village head in mobilizing community participation in gotong royong activities. community participation in gotong royong activities, c) The role of the village head in overseeing community participation in mutual cooperation activities gotong royong activities, d) The role of the village head in increasing community participation in d) The role of the village head in increasing community participation in gotong royong activities using descriptive and qualitative approaches. descriptive with a qualitative approach. The results in this study are, a) The village head has a role in planning the gotong royong activities of the village head. must consider the situation and conditions of the existing residents so that residents will follow the gotong royong activities. b) The village head plays a role in mobilizing residents to take part in mutual cooperation activities. residents to participate in gotong royong activities because the village head must provide examples or examples that can motivate residents to participate in mutual cooperation activities and the village head has .